Frontline Science: Late CD27 stimulation promotes IL‐7Rα transcriptional re‐expression and memory T cell qualities in effector CD8+ T cells. Issue 5 (14th June 2019) - Dong, Han; Buckner, Andrew; Prince, Jessica; Bullock, Timothy
Abstract: We previously demonstrated that CD27 co‐stimulation during a primary CD8 + T‐cell response was critical for the expression of IL‐7Rα on acute effector CD8 + T cells, providing an essential element in the generation of CD8 + T‐cell memory to infectious pathogens. IL‐7 plays a critical role in the generation and maintenance of memory CD8 + T cells, and IL‐7Rα has been regarded as a functional marker of long‐lived memory precursor effector cells. While IL‐7Rα is downregulated acutely upon TCR stimulation, the regulation of the emergence of IL‐7Rα expressing cells around the peak of primary CD8 + responses is less clear. Re‐expression could be a default outcome after withdrawal of TCR stimulation. Alternatively, specific stimuli could actively antagonize the downregulation or promote the recovery of IL‐7Rα in Ag‐activated CD8 + T cells. By utilizing agonistic mAb and transgenic models, here we show: (1) CD27 stimulation acts directly on CD8 + T cells to enhance IL‐7Rα‐expressing effectors; (2) CD27 stimulation neither alleviates the downregulation of IL‐7Rα upon TCR signaling nor promotes the expansion/survival of IL‐7Rα‐expressing effectors, but facilitates IL‐7Rα re‐expression; (3) CD27 stimulation regulates Il7ra mRNA abundance but not protein distribution. Importantly, CD27 stimulation promotes not only IL‐7Rα, but also the common γ chain of the receptor and the downstream signaling mediated by pSTAT5. Our results demonstrate a previously unappreciated role of CD27 stimulation as a positive regulator of IL‐7Rα during CD8 T‐cell responses, provide insights into the mechanistic basis by which CD27 stimulation influences CD8 + T‐cell memory differentiation, and highlight the potential of targeting CD27‐CD70 axis to enhance IL‐7 signaling for antiviral/antitumor immunotherapy. Abstract : Late CD27 stimulation promotes CD8+ T cell memory differentiation by increasing transcription of IL7Rα and γc.